Aging alters face expressions processing and recognition: insights on possible neural mechanisms - Ginatempo, Francesca; Loi, Nicola; Zeroual, Mohammed; Cadoni, Marinella; Fadda, Mauro; Lagorio, Andrea; Deriu, Franca (Journal of neurophysiology, 2025)
The study of the face expression processing in young and senior subjects evidenced that aging alters the fixation pattern for face expressions by reducing the visual attention toward sad faces. This alteration is associated with a reduced intracortical inhibition in face primary motor cortex, which correlates with compromised recognition abilities for sad face expressions. The present work investigated how aging influences the different stages of face expression processing: fixation patterns, early perception, face motor response, and recognition. Thirty-four participants (17 young, 17 senior) were subjected to 1) recording of fixation patterns, 2) recording of the P100 and the N170 components of event-related potentials, 3) excitability of short intracortical inhibition (SICI) and intracortical facilitation (ICF) of the face primary motor cortex (face M1), and 4) recognition task during the passive viewing of neutral, happy, and sad faces expressions. Senior subjects mostly looked at the mouth, had reduced pupil size, and delayed N170 latency, regardless of expression, compared with young subjects, and a reduced P100 amplitude when viewing sad faces. Senior subjects’ excitability of face M1 was enhanced compared to the young group; both groups had a reduced SICI when viewing happy faces, but only senior subjects exhibited reduced SICI for sad faces. Young subjects had better recognition accuracy and response times than senior ones, particularly for sad expressions. When viewing sad expressions, SICI was negatively correlated with recognition accuracy. Data suggested that aging reduces visual attention for sad faces, which appears to be connected to an increased excitability of face M1, which in turn is linked to their impaired recognition skills, especially when processing negative face expressions. These findings provide new insights into the comprehension of how aging affects cognitive functions and the process of face expression recognition. NEW & NOTEWORTHY The study of the face expression processing in young and senior subjects evidenced that aging alters the fixation pattern for face expressions by reducing the visual attention toward sad faces. This alteration is associated with a reduced intracortical inhibition in face primary motor cortex, which correlates with compromised recognition abilities for sad face expressions.